Imunoexpressão da proteína galectina-3 no câncer colorretal e sua relação com sobrevida - Povegliano, Luciana Zaia Della Negra [UNIFESP] (2008)
Backgrounds: Colorectal cancer is one of most common tumors nowadays. The survival and the disease-free survival are enhanced because of new chemotherapy drugs. Tumor biological markers will contribute for a better treatment. Galectin-3 is an endogenous galactose-binding protein that is expressed in a wide range of normal and neoplastic tissues and is thought to be involved in cellular adhesion, growth regulation and apoptosis. Galectin-3 is already studied in thyroid cancer, and seems to have an important role in colorectal cancer. Objective: Evaluate the immunoexpression of galectin-3 protein in patients with colorectal cancer under surgery and resection of the tumor and chemotherapy treatment and the relationship of galectin-3 expression and tumor evolution and clinical aspects. Methods: We studied the expression of galectin-3 in 75 colorectal tissues. An immunohistochemical scoring system was used to evaluate the cytoplasmic cells color. We divided the tumor’s cells in two groups: group 1, absent or weak (less than 50% staining cells) and group 2 strong or moderate ( 50% staining cells). Results: Among the 75 patients, 40 were female; the average age was 61.98 years old (from 29 to 86 years old). According to the site, 42.6% was of rectum, 33.4% right colon and 24% left colon. 33 tumors were stage II, 32 stage III and 10 stage IV. Galectin-3 immunoexpression was classified as 1 in 57.33% of tumors. The highest stage appears in the most staining cells (score 2 in 60% of tumors IV, 40.63% in tumors stage III and 39.39% in stage II, p=0.4899). In addition, galectin-3 immunoexpression group 1 showed higher survival (65.96% of no disease patient with galectin-3 group 1 and 34.04% group 2). On the other hand, in the group of patients with metastatic disease the results were 52.63% in group 1 and 47.37% in group 2 (p=0.0465). Conclusion: The imunoexpression of galectin-3 was strong or moderate in 42% of the colorectal tumors. Correlation among sex, age, stage, site or metastases and galectin-3 were not observed. Patients with strong or moderate imunoexpression of the protein in higher proportions died or had recurrence more frequently. The risk of death was marginally reduced in patients with negative or low grade galectin-3. Galectin-3 citoplasmatic immunoexpression seems to be a prognostic factor in colorectal cancer.